Extracellular vesicles from immortalized cardiosphere-derived cells attenuate arrhythmogenic cardiomyopathy in desmoglein-2 mutant mice. (29th July 2021) - Lin, Yen-Nien; Mesquita, Thassio; Sanchez, Lizbeth; Chen, Yin-Huei; Liu, Weixin; Li, Chang; Rogers, Russell; Wang, Yizhou; Li, Xinling; Wu, Di; Zhang, Rui; Ibrahim, Ahmed; et al.
Abstract: Aims: Arrhythmogenic cardiomyopathy (ACM) is characterized by progressive loss of cardiomyocytes, and fibrofatty tissue replacement. Extracellular vesicles (EVs) secreted by cardiosphere-derived cells, immortalized, and engineered to express high levels of β-catenin, exert anti-inflammatory, and anti-fibrotic effects. The aim of the current study was to assess efficacy of EVs in an ACM murine model. Methods and results: Four-week-old homozygous knock-in mutant desmoglein-2 (Dsg2 mt/mt ) were randomized to receive weekly EVs or vehicle for 4 weeks. After 4 weeks, DSG2 mt/mt mice receiving EVs showed improved biventricular function (left, P < 0.0001; right, P = 0.0037) and less left ventricular dilation ( P < 0.0179). Electrocardiography revealed abbreviated QRS duration ( P = 0.0003) and QTc interval ( P = 0.0006) in EV-treated DSG2 mt/mt mice. Further electrophysiology testing in the EV group showed decreased burden ( P = 0.0042) and inducibility of ventricular arrhythmias ( P = 0.0037). Optical mapping demonstrated accelerated repolarization ( P = 0.0290) and faster conduction ( P = 0.0274) in Dsg2 mt/mt mice receiving EVs. DSG2 mt/mt hearts exhibited reduced fibrosis, less cell death, and preserved connexin 43 expression after EV treatment. Hearts of Dsg2 mt/mt mice expressed markedly increased levels of inflammatory cytokines that were, in part, attenuated by EV therapy. The pan-inflammatory transcription factor nuclear factor-κB (NF-κB), the inflammasome sensor NLRP3, and the macrophage marker CD68 were all reduced in EV-treated animals. Blocking EV hsa-miR-4488 in vitro and in vivo reactivates NF-κB and blunts the beneficial effects of EVs. Conclusions: Extracellular vesicle treatment improved cardiac function, reduced cardiac inflammation, and suppressed arrhythmogenesis in ACM. Further studies are needed prior to translating the present findings to human forms of this heterogenous disease. Graphical abstract: